2001
DOI: 10.1093/genetics/159.1.241
|View full text |Cite
|
Sign up to set email alerts
|

technical knockout, a Drosophila Model of Mitochondrial Deafness

Abstract: Mutations in mtDNA-encoded components of the mitochondrial translational apparatus are associated with diverse pathological states in humans, notably sensorineural deafness. To develop animal models of such disorders, we have manipulated the nuclear gene for mitochondrial ribosomal protein S12 in Drosophila (technical knockout, tko). The prototypic mutant tko25t exhibits developmental delay, bang sensitivity, impaired male courtship, and defective response to sound. On the basis of a transgenic reversion test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…Analysis of the patient showed a homozygous C-to-T substitution at nucleotide 331 of the MRPS16 cDNA (Miller et al, 2004). Similar results showed that in Drosophila, a missense mutation in mitochondrial ribosomal protein S12 prevented ribosomal proteins from assembling into active ribosomes, resulting in a significant reduction in 12S rRNA transcripts (Toivonen et al, 2001). Another mitochondrial ribosomal SSU protein mutation occurs in MRPS22.…”
Section: Mrps Mutationssupporting
confidence: 55%
“…Analysis of the patient showed a homozygous C-to-T substitution at nucleotide 331 of the MRPS16 cDNA (Miller et al, 2004). Similar results showed that in Drosophila, a missense mutation in mitochondrial ribosomal protein S12 prevented ribosomal proteins from assembling into active ribosomes, resulting in a significant reduction in 12S rRNA transcripts (Toivonen et al, 2001). Another mitochondrial ribosomal SSU protein mutation occurs in MRPS22.…”
Section: Mrps Mutationssupporting
confidence: 55%
“…Furthermore, mutations in mitochondrial rRNA transfer and mitochondrial aminoacyl tRNA synthetase genes were identified as causative of deafness (30,31). Mutation of the mitochondrial ribosomal protein S12 (technical knockout, tko) was also reported as a cause of deafness in fruit flies (32). Taken together, these observations strongly indicate functional associations between defects of mitochondrial translation machinery and hearing loss.…”
Section: Mitochondrial Gene Expression and Hearing Lossmentioning
confidence: 93%
“…Courtship was analyzed essentially as previously (Toivonen et al 2001), in batches of 6 pairs of adult male and virgin female 3 day-old flies of a given genotype. For experiments at different temperatures, virgin flies were kept at the experiment temperature until the experiment was started.…”
Section: Courtship Analysismentioning
confidence: 99%